Orthodontic tooth movement in immature ápices: a systematic review - Isaac Wasserman-Milhem; Mayra Lizbeth Bravo-Casanova; Félix Alexander Caraballo-Moreno; Diana Antonia Granados-Pelayo; Claudia Patricia Restrepo-Bolívar (Universidad de Antioquia, 2016)
Introduction: orthodontic tooth movement with open apices which have not completed root formation has not been sufficiently studied. There is controversy about the risks associated to this movement, such as root resorption and decreased root length. The goal of this systematic review is to determine the possible effects of lengthening, shortening, or root resorption possibly occurring during orthodontic movement in teeth that have not completed root formation. Methods: electronic search (PubMed, Cochrane, Dentistry and Oral Sciences Source, Science Direct, Google Scholar, IdeA, ProQuest, Embase, Medline, Lilacs, TRIP) and manual search at Universidad El Bosque Juan Roa Vázquez Library since 1990 to 2014. Articles meeting the inclusion criteria, such as randomized clinical trials, prospective and retrospective studies, and studies in early mixed dentition with 2 x 4 system, were evaluated and methodologically qualified by four researchers. Results: this study involved a custom methodological rating taken from Lagravere et al (2005). Four articles were finally selected, three of which were retrospective: Amlani et al (2007), with 26 patients, found root resorption in 8% of the sample, with no statistical significance. Mavragani et al (2002), with a sample of 146 patients, found longer roots in younger teeth, and Kim & Park (2004), with 59 patients, found higher resorption in maxillary lateral incisors. Da Silva et al (2005), with 46 patients, reported a prevalence of 4.4% in root resorption in central incisors. Conclusions: this systematic review must be taken cautiously due to the low and moderate level of evidence found. In general terms, there were no alterations in terms of root length or shape when teeth with open apices were subjected to fixed orthodontic forces. The risk of apical resorption was more related to treatment duration in teeth with both open and closed apexes.